Steganalysis Using Wavelet Transform - Waleed . A Mahmud; Talib M Jawad; Hussam Juma'a Nayma (Journal of Kufa for Mathematics and Computer, 2012)
Techniques and applications for information hiding have become increasingly more sophisticated and widespread. With high-resolution digital images as carriers, detecting the presence of hidden messages has also become considerably more difficult. It is sometimes possible, nevertheless, to detect (but not necessarily decipher) the presence of embedded messages. The basic approach taken here works by finding predictable higher-order statistics of "natural" images within a multi-scale decomposition, and then showing that embedded messages alter these statistics.